The Political Economy of Multidimensional Child Poverty Measurement : A Comparative Analysis of Mexico and Uganda - Cuesta, Jose; Biggeri, Mario; Hernandez-Licona, Gonzalo; Aparicio, Ricardo; Guillen-Fernandez, Yedith (Taylor and Francis, 2021)
As part of the 2030 Agenda, much effort has been exerted in comparing multidimensional child poverty measures both technically and conceptually. Yet, few countries have adopted and used any of these measures in policymaking. This paper explores the reasons for this absence from a political economy perspective. It develops an innovative political economy framework for poverty measurement and a hypothesis whereby a country will only produce and use reliable and sustainable multidimensional child poverty (MDCP) measures if and only if three conditions coalesce: consensus, capacity and polity. We explore this framework with two relevant case studies, Mexico and Uganda. Both countries satisfy the capacity condition required to measure MDCP but only Mexico satisfies the other two conditions. Our proposed political economy framework is normatively relevant because it identifies the conditions that need to change across multiple contexts before the effective adoption and use of an MDCP measure becomes more likely.